Macronutrients modified dietary intervention in the management of overweight/obese children and adolescents: a systematic review - Jihyun Park; Oh Yoen Kim (The Korean Pediatric Society, 2024)
The prevalence of obesity in adults and children is rapidly increasing worldwide. Obesity is among the main causes of chronic diseases and various problems, including economic consequences and they can also be affected by genetic, environmental, psychological, and socioeconomic factors. Dietary modification is a well-known and important factor in weight control, in particular, dietary macronutrient composition, food selection, dietary patterns, and energy restriction can affect weight reduction. Therefore, this systematic review aims to provide basic evidence for identifying the optimal macronutrient composition for managing obesity in Korean children and adolescents. We searched literature through an international database, studies were selected using our eligibility criteria and quality was assessed via a risk of bias tool. In our results, several studies have demonstrated that dietary macronutrient modifications affect body composition and metabolic markers in children and adolescents. In contrast, hypocaloric diets, regardless of macronutrient composition, are reportedly effective for weight loss in obese children. However, these findings were based on intervention studies that examined the association between dietary macronutrient composition and obesity in non-Korean children and adolescents. Therefore, in the future, more intervention studies are needed to elucidate this relationship and evidence between macronutrients and obesity in Korean children and adolescents.